Reconstruction of Moderate Religious Education Based on Inclusivity Values at Salafi Pesantren - Fihris, Fihris; Nasikhin, Nasikhin; Nuzula, Firda Rahmatun; Waeduereh, Mustafakamal; Ta'rifin, Ahmad (EDUKASIA, 2025)
This study aims to analyze efforts to reconstruct religious moderation education based on inclusive values at Salaf Islamic School, focusing on strategies, student responses, and challenges faced in its implementation. Using a qualitative approach with a case study design, data were collected through in-depth interviews with religious scholars, teachers, and students, as well as participant observation. Data analysis was conducted thematically based on the Miles and Huberman model—including data reduction, data presentation, and conclusion drawing. The results revealed that the implementation of three main strategies—(1) curriculum integration that combines religious teachings with national values, human rights, and tolerance; (2) dialogic learning methods that foster critical thinking and active participation; and (3) the creation of an inclusive environment through cross-community social activities and the acceptance of students from diverse backgrounds—had a significant impact on fostering moderate and open attitudes among students. The majority of students demonstrated increased empathy, openness to differences, and commitment to a harmonious national life, although a small number still resisted due to the influence of exclusive ideologies. Despite facing challenges such as limited resources, cultural resistance, and pressure from conservative groups, the Islamic boarding school managed to maintain this transformation through teacher training, internal dialogue, and external partnerships. These findings not only demonstrate that traditional religious education can be revitalized into an effective vehicle for contextual and inclusive religious moderation, but also offer a concrete model that can be replicated by other Salafi Islamic boarding schools in an effort to counter radicalism and strengthen social cohesion amidst the fragmentation of contemporary society.